2016
DOI: 10.4187/respcare.04619
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Targeted Versus Pressure-Limited Noninvasive Ventilation in Subjects With Acute Hypercapnic Respiratory Failure: A Multicenter Randomized Controlled Trial

Abstract: Regardless of whether a VT- or PL-NIV strategy is employed, it is possible to provide similar support to subjects with AHRF. (ClinicalTrials.gov registration NCT02538263.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Despite this, no difference between groups was seen in the course of CO 2 improvement, duration of NIV or length of hospital stay. These findings echo those of another randomized trial comparing BPAP‐ST to Va‐BPAP‐ST performed on general respiratory wards in patients with acute hypercapnic respiratory failure . Reductions in PaCO 2 after 2 and 6 h of therapy, need for intubation and in‐hospital mortality did not differ between therapy modes.…”
Section: Volume‐assured Pressure Supportsupporting
confidence: 81%
“…Despite this, no difference between groups was seen in the course of CO 2 improvement, duration of NIV or length of hospital stay. These findings echo those of another randomized trial comparing BPAP‐ST to Va‐BPAP‐ST performed on general respiratory wards in patients with acute hypercapnic respiratory failure . Reductions in PaCO 2 after 2 and 6 h of therapy, need for intubation and in‐hospital mortality did not differ between therapy modes.…”
Section: Volume‐assured Pressure Supportsupporting
confidence: 81%
“…1 We agree that P aO 2 /F IO 2 could not be accurately calculated in our study, because supplemental oxygen was delivered through a port in the mask, and the noninvasive ventilator that we used did not provide accurate F IO 2 .…”
Section: P Ao 2 /F Io 2 Is Not a Guestimationreplymentioning
confidence: 55%
“…This ventilatory strategy has been demonstrated to be useful in patients with chronic respiratory insufficiency [6,7] and in subjects with acute hypercapnic respiratory insufficiency [8,9]. Briones Claudett et al [8] reported the first case-control study with benefits in 11 subjects with COPD and hypercapnic encephalopathy.…”
mentioning
confidence: 99%
“…Briones Claudett et al [8] reported the first case-control study with benefits in 11 subjects with COPD and hypercapnic encephalopathy. Cao et al [9] described the results from a multi-centre randomised controlled trial comparing pressure-limited NIV versus volume-targeted NIV in 58 subjects with acute hypercapnic respiratory failure who had underlying chronic obstructive pulmonary disease (COPD). Ciftci Fatma, et al [10] evaluated the feasibility of using BiPAP S/T-AVAPS.…”
mentioning
confidence: 99%